THE IMPLEMENTATION OF WEB-BASED FORWARD CHAINING AS AN EXPERT SYSTEM FOR DIAGNOSIS OF CATTLE DISEASE IN CENTRAL LAMPUNG (CASE STUDY: CATTLE FARM IN BANJAR SARI) - Novita Andriyani; Doni Irawan (International Journal of Artificial Intelligence and Robotic Technology, 2021)
The potential of livestock in Central Lampung Regency has a great influence on most markets, because this is the largest livestock farming area in Lampung Province. Farmers in Indonesia often encounter various diseases in their livestock. In Central Lampung, many farmers know that their cattle are infected with certain diseases which cause farmers to experience losses in raising cattle because they are not suitable for trading. In this modern era, people must understand the problems they face. One of them is how to deal with the livestock industry when a cow is infected with a certain virus. Some breeders are confused about what disease will attack the cow so that it has the potential to get disease. An expert system is a digitalization model which transfers knowledge from an expert to a machine or program. In this case, the expert system is one way to solve the problem of cattle farming in Central Lampung. By using the Forward Chaining method and website-based implementation which is one way to solve expert system problems, this can make it easier for the community and cattle breeders to understand the disease and how to overcome it without spending too much money.